Design of parity generator and checker circuit using electro-optic effect of Mach–Zehnder interferometers - Kumar, Santosh; Chanderkanta, Chanderkanta; Amphawan, Angela (Elsevier B.V., 2016)
Parity is an extra bit which is used to add in digital information to detect error at the receiver end.It can be even and odd parity.In case of even parity, the number of one's will be even included the parity and reverse in the case of odd parity.The circuit which is used to generate the parity at the transmitter side, called the parity generator and the circuit which is used to detect the parity at receiver side is called as parity checker.In this paper, an even and odd parity generator and checker circuits are designed using electro-optic effect inside lithium niobate based Mach–Zehnder Interferometers (MZIs).The MZIs structures collectively show powerful capability in switching an input optical signal to a desired output port from a collection of output ports. The paper constitutes a mathematical description of the proposed device and thereafter simulation using MATLAB.The study is verified using beam propagation method (BPM).